A study on the critical effects of the existing malls on the businesses in Iloilo City Proper - Abunda, Anabelle T.; Ambong, Ma. Erna A.; Ceñidoza, Clovell M.; Jarbadan, Jasmin A.; Santiago, Joy G. (Iloilo City University of the Philippines in the Visayas, College of Management, 1998)
This study aims to find out the critical effects of the existence of malls on the businesses in Iloilo City Proper. In the first chapter, the researchers present the objectives of this undertaking : to find out the target maket of each business ; buyers' shopping center preference, reasons thaat motivate buyers to patronize a specific shopping center ; to compare the operating performance of each business for the period covered 1993-97 ; and to determine the strategies employed by each business to stay competitive in the market. The business under study are drugstores, novelty shops, boutiques, grocery stores, textiles, and bookstores. chapter two presents the related lterature cited in and supporting the findings of the study. The researchers used prior studies conducted by the Wall Street Journal on September 19, 1989 and the latest of which was conducted on 1995 by Marilou Lavega and Salvacion Panilla of UP in the Visayas, College of Management as reference in this undertaking. The researchers focused their attention on the consumer's behavior as a determining factor of their buying preferences. Furthermore, the researchers were able to enumerate several categories of buying motives as defined by Richard D. Steade, James R. Lowry, and Raymond E. Glos. In the conceptual framework, Maslow's theory of man's hierarchy of need was discussed together with the SWOT analysis concept which are tools for studying the internal and external environment of business. Chapter three states the methods and procedures used by the researchers in the data gathering. This includes data collection procedures such as distribution of questionnaires, interviews, and library research. In this study the researchers used a purposive or judgmental sampling method. Chapter four involves the presentation of data gathered and the interpretations as related to the proposed solutions. The researchers were able to come up with twenty-two (22) tables based on the questions formulated in the questionnaire that was distributed. Frequency tables are used to served as the basis for the analyses presented in the undertaking. Chapter five, as the last chapter consists of the summary of results and findings, conclusions, and recommendations. As expected, the existence of malls proved to have critical effects on the businesses in Iloilo City Proper. The survey revealed that in a period of five years (1993-97) independent stores experienced increasing rent expenses, inventory purchase cost, financial difficulties, selling prices, credit sales, and greater number of products to offer. Also, relevant decrease in certain aspects such as sales performance, numbers of customers frequenting their stores, number of personnel, and advertising or promotions. Considering these matters, there's a need for the management of affected business establishments to reconsider their business policies and strategies to keep pace with competitive challenge posed by malls. Based on the survey the leading strategy is the improvement of services offered, which most of the respondents considered renovating of establishment as a good strategy.
Research Paper (BA 200 - Business Research) -- [Iloilo City] : UPV-CM, March 27, 1998.